Role of Innate Immune Response in Non-Alcoholic Fatty Liver Disease: Metabolic Complications and Therapeutic Tools - Meli, Rosaria; Mattace Raso, Giuseppina; Calignano, Antonio (Frontiers in Immunology, 2014)
Non-alcoholic fatty liver disease (NAFLD) is currently the most common liver disease worldwide, both in adults and children. It is characterized by an aberrant lipid storage in hepatocytes, named hepatic steatosis. Simple steatosis remains a benign process in most affected patients, while some of them develop superimposed necroinflammatory activity with a non-specific inflammatory infiltrate and a progression to non-alcoholic steatohepatitis with or without fibrosis. Deep similarity and interconnections between innate immune cells and those of liver parenchyma have been highlighted and showed to play a key role in the development of chronic liver disease. The liver can be considered as an “immune organ” because it hosts non-lymphoid cells, such as macrophage Kupffer cells, stellate and dendritic cells, and lymphoid cells. Many of these cells are components of the classic innate immune system, enabling the liver to play a major role in response to pathogens. Although the liver provides a “tolerogenic” environment, aberrant activation of innate immune signaling may trigger “harmful” inflammation that contributes to tissue injury, fibrosis, and carcinogenesis. Pathogen recognition receptors, such as toll-like receptors and nucleotide oligomerization domain-like receptors, are responsible for the recognition of immunogenic signals, and represent the major conduit for sensing hepatic and non-hepatic noxious stimuli. A pivotal role in liver inflammation is also played by cytokines, which can initiate or have a part in immune response, triggering hepatic intracellular signaling pathways. The sum of inflammatory signals and deranged substrate handling induce most of the metabolic alteration traits: insulin resistance, obesity, diabetes, hyperlipidemia, and their compounded combined effects. In this review, we discuss the relevant role of innate immune cell activation in relation to NAFLD, the metabolic complications associated to this pathology, and the possible pharmacological tools.